Pengaruh Bimbingan Kelompok Teknik Problem Solving Terhadap Strategi Manajemen Konflik Anggota KIR - Surianingsih, Yulia (Universitas Negeri Semarang, 2017)
Conflict is usual had experienced by somebody. Somebody is as social people in interact with other will have a conflict. If conflict hadn’t overcame with appropriate strategy, it will give bad impact. This study purposed to know effect of group guidance services by problem solving technique for increatment the conflict manajement strategy. This study is experimental study. This study was conducted at Student Sains Group in 11 SHS of Semarang State with ten students as the sample. The data were collected by conflict manajement stategy scale. The data analysis technique used descriptive percentage analysis and wilcoxon match pairs analysis. The result of descriptive percentage showed that conflict manajement of student before students are given group guidance services by game technique is in the average high category (74%) and after obtaining group guidance services by problem solving technique have an average in the high category (85%). Based on the wilcoxon match pairs test showed that tcount = 0 and ttable = 8, so tcount < ttable, then Ha is accepted and Ho is rejected. The result, showed group guidance services with problem solving technique have a effect for conflict manajement strategy. This study give important contribution in aplication of guidance dan counseling at school.